Non-exercise estimated cardiorespiratory fitness and cancer incidence: The NIH-AARP diet and health study - Baruch Vainshelboim; Jonathan Myers; Charles E. Matthews (Elsevier, 2023)
Background: Non-exercise estimated cardiorespiratory fitness (NEE-CRF) has been shown to be associated with mortality, although its association with cancer incidence is unknown. The study aimed to assess the prospective association between NEE-CRF and cancer incidence in a large cohort of men and women. Methods: The National Institutes of Health-American Association of Retired Persons diet and health study is a prospective cohort that included 402,548 participants aged 50-71 years who were free from cancer at baseline (1995-1996) (men (n = 238,835) and women (n = 163,713)) and were followed until December 31, 2015. The exposure variable was NEE-CRF expressed in metabolic equivalents. NEE-CRF was estimated using a validated equation of self-reported predictors on demographics and lifestyle behaviors derived from baseline questionnaires. Primary outcomes were total cancer incidence and incidence of prostate, breast, lung, and colorectal cancers. Cox proportional hazards models were analyzed for the association between NEE-CRF and cancer incidence outcomes adjusted for established cancer risk factors. Results: During 13.7 ± 3.2 years of follow-up (mean ± SD), 64,344 men and 31,315 women developed a new cancer. For every 1-metabolic equivalent higher NEE-CRF, the hazard ratios and 95% confidence intervals (95%CIs) were 0.96 (95%CI: 0.94-0.97) and 0.88 (95%CI: 0.84-0.92) of total and colorectal cancer incidence among men, and 0.95 (95%CI: 0.93-0.97) and 0.94 (95%CI: 0.91-0.97) of total and breast cancer incidence among women, respectively (all p < 0.001). NEE-CRF was not associated with incidence of prostate and lung cancers in men or colorectal and lung cancers in women. Conclusion: These results suggest that higher CRF levels, as assessed by the applied non-exercise estimated method, may provide preventive benefits against the development of cancer, while low CRF could potentially serve as a modifiable cancer risk factor. Integrating NEE-CRF into screening paradigms and referring low-fit individuals to improve CRF could complement the public health prevention strategy against cancer.